What Motivational Factors Affect Those Entering Public Sector Organizations? The Case of a Power Company - Barreto, Daniela F. da C.; Nunes, Glaucio Santoro; Veiga, Jordana L. B. C.; Boas, Ana Alice Vilas (Revista Gestão da Produção Operações e Sistemas, 2007)
Job opportunities in the public sector have interested a growing number of individuals who opt for this path in searchof stability, quality of life, opportunities to build a career, training and benefits, among other advantages offered. Theobjective of this study was to verify the factors that motivated a group of people to opt for public sector employment,more specifically, in a large, mixed economy company in the technology and energy sector. The answers from thesepeople, who are currently employees, were gathered by means of a structured interview and questionnaire. They arerevealed in this article and compared to the results presented in the article by Côrtes and Silva (20060. The tendencyin the answers given to most of the questions was the same in both studies. The results show that stability and companyimage were the most indicated factors as motivators for entering a state-owned company.Keywords: Motivational Theories, Psychological Contract, Public Sector